Classification of Perinatal Ischemic Stroke - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2009)
Advances in classification, causes, treatment and outcome of perinatal ischemic stroke are reviewed by researchers at Alberta Children's Hospital, Calgary; and the Hospital for Sick Children, Toronto, Canada.